Online shopping routines among chilean children: level of expansion and main causes - Feijoo, Beatriz; García González, Aurora (Faculty of Mass Media Communication at the University SS. Cyril and Methodius in Trnava, Slovakia, 2020)
This research focuses on the last phase of advertising1 and seeks to analyse the frequency of purchase via mobile devices by children and adolescents (aged 10 to 14) living in the Metropolitan Region of Santiago de Chile. The interest in this particular cohort stems from the fact that recent studies have shown that online purchases have increased significantly among Chileans. The study addresses online shopping tendencies among children based on how they respond to the advertising they are exposed to through their mobile devices. Specifically, the text analyses the level of expansion, reasons for online purchases, access and payment, and interest categories, among other issues. To this avail, a survey was conducted in 501 households in the Metropolitan Region of Santiago de Chile. The results show that less than 10% of the respondents said they had made online purchases over the last year, and among those who had made purchases, most of these corresponded to the acquisition of video games, event tickets and clothing. Nearly 50% stated that online purchases were motivated by lower prices or access to promotions. This research aims to contribute to establishing a solid starting point and promote subsequent research on better child rearing practices, content supervision and parental and social mediation.
Keywords: advertising; children; consumer; e-commerce; mobile devices; online shopping; screens; Scopus; Emerging